2022
DOI: 10.3389/fpsyg.2022.954299
|View full text |Cite
|
Sign up to set email alerts
|

Destination image, nostalgic feeling, flow experience and agritourism: An empirical study of Yunling Tea Estate in Anxi, China

Abstract: This study introduces destination image, nostalgic feeling, and flow experience into tea estate tourism and constructs a theoretical model that includes destination image, nostalgic feeling, flow experience, cultural identity, and tourists’ behavioral intention. Then, an empirical study is conducted with tourists at Yunling Tea Estate in Anxi, China. The results show that all hypotheses are supported except the hypothesis pertaining to the significance of the influence of flow experience on behavioral intentio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…Contrasting with covariance-based structural equation modeling (CB-SEM), partial least squares structural equation modeling (PLS-SEM) requires a smaller sample size [ 30 , 31 ] and can handle non-normal data [ 32 ]. Additionally, PLS-SEM excels at addressing issues of multicollinearity, making it highly suitable for exploratory analysis and validation of constructed model structures.…”
Section: Model Establishment and Data Sourcesmentioning
confidence: 99%
“…Contrasting with covariance-based structural equation modeling (CB-SEM), partial least squares structural equation modeling (PLS-SEM) requires a smaller sample size [ 30 , 31 ] and can handle non-normal data [ 32 ]. Additionally, PLS-SEM excels at addressing issues of multicollinearity, making it highly suitable for exploratory analysis and validation of constructed model structures.…”
Section: Model Establishment and Data Sourcesmentioning
confidence: 99%
“…Drawing from the prevailing cognitive-behavioral and satisfaction theories, extensive research has concentrated on examining the interaction between perceptions and the behavior of tea tourists [12,14]. Scholars have demonstrated diversity in their choice of constructs, driven by distinct research objectives.…”
Section: Tourists' Behavior In Tea Tourism and Its Influencing Factorsmentioning
confidence: 99%
“…Mondal and Samaddar [13] established a correlation between tourists' attitudes and their behavioral patterns. Furthermore, Zhang et al [14] identified that elements such as destination image, nostalgic feelings, flow experiences, and cultural identity significantly impact tourists' behavior intentions within the realm of tea tourism. Chanin et al [17] enhance the discourse by accentuating the importance of sustainable livelihood, subjective norms, and attitudes in shaping tourists' intentions to revisit.…”
Section: Tourists' Behavior In Tea Tourism and Its Influencing Factorsmentioning
confidence: 99%
See 2 more Smart Citations